Use of Web-Based E-Learning Applications in Arabic Learning at Madrasah Sanawiah, Sidoarjo Regency - Shabryna Mathovani; Doni Septi (Indonesian Journal of Islamic Studies, 2022)
This article aims to determine the process of learning Arabic through a web-based E-learning application at MTs NU Durung Bedug Candi Sidoarjo. The research method used by the researcher is a qualitative descriptive approach. The results of the study indicate that, 1. Providing socialization of web-based E-learning applications before learning begins for teachers. 2. use of media in the form of video links, Microsoft word, and assignments that will be included in the web-based E-learning application and sometimes if you don't understand, an online meeting will be held via Gmeet or zoom. 3. Stages of school evaluation conducting PTS and PAS using the CBT system (computer basic test). For the week using a web-based E-learning application by entering questions that have been made by the Arabic language teacher. 4. Students' problems in using this application are from the lack of quotas, students' self-awareness in collecting assignments and lack of facilities.